Efficient Reovirus- and Measles Virus-Mediated Pore Expansion during Syncytium Formation Is Dependent on Annexin A1 and Intracellular Calcium - Ciechonska, Marta (American Society for Microbiology, 2014)
Orthoreovirus fusion-associated small transmembrane (FAST) proteins are dedicated cell-cell fusogens responsible for multinucleated syncytium formation and are virulence determinants of the fusogenic reoviruses. While numerous studies on the FAST proteins and enveloped-virus fusogens have delineated steps involved in membrane fusion and pore formation, little is known about the mechanics of pore expansion needed for syncytiogenesis. We now report that RNA interference (RNAi) knockdown of annexin A1 (AX1) expression dramatically reduced both reptilian reovirus p14 and measles virus F and H protein-mediated pore expansion during syncytiogenesis but had no effect on pore formation. A similar effect was obtained by chelating intracellular calcium, which dramatically decreased syncytiogenesis in the absence of detectable effects on p14-induced pore formation. Coimmunoprecipitation revealed calcium-dependent interaction between AX1 and p14 or measles virus F and H proteins, and fluorescence resonance energy transfer (FRET) demonstrated calcium-dependent p14-AX1 interactions in cellulo. Furthermore, antibody inhibition of extracellular AX1 had no effect on p14-induced syncytium formation but did impair cell-cell fusion mediated by the endogenous muscle cell fusion machinery in C2C12 mouse myoblasts. AX1 can therefore exert diverse, fusogen-specific effects on cell-cell fusion, functioning as an extracellular mediator of differentiation-dependent membrane fusion or as an intracellular promoter of postfusion pore expansion and syncytium formation following virus-mediated cell-cell fusion. IMPORTANCE Numerous enveloped viruses and nonenveloped fusogenic orthoreoviruses encode membrane fusion proteins that induce syncytium formation, which has been linked to viral pathogenicity. Considerable insights into the mechanisms of membrane fusion have been obtained, but processes that drive postfusion expansion of fusion pores to generate syncytia are poorly understood. This study identifies intracellular calcium and annexin A1 (AX1) as key factors required for efficient pore expansion during syncytium formation mediated by the reptilian reovirus p14 and measles virus F and H fusion protein complexes. Involvement of intracellular AX1 in syncytiogenesis directly correlates with a requirement for intracellular calcium in p14-AX1 interactions and pore expansion but not membrane fusion and pore formation. This is the first demonstration that intracellular AX1 is involved in pore expansion, which suggests that the AX1 pathway may be a common host cell response needed to resolve virus-induced cell-cell fusion pores.